The song structure of Cicadetta podolica (Eichwald 1830) (Hemiptera: Cicadidae) - Trilar, Tomi (Acta entomologica slovenica (Ljubljana), 2007)
Using recording equipment for sonic and ultrasonic range we recorded the calling and the courtship songs of Cicadetta podolica (Eichwald 1830) in Krzyżanowice Dolne near Pińczów in Poland. Cicadetta podolica is a steppe species and belongs to the Cicadetta montana species complex. The calling song structure of C. podolica is characteristic and easily distinguishable from the songs of related cicadas. The whole phrase of calling song can be as short as 1.2 s or longer than 5.2 s but the typical phrase duration is 3.3 0.9 seconds. The next phrase begins after a three quarters of a second long pause. Each phrase consists typically of a long sequence of short echemes (duration 1.6 0.6 s) repeated about 12 1 times per second and ending with one long echeme (duration 1.6 0.6 s). The song contains frequencies from 7.5 to 20.5 kHz with a maximum between 9.9 and 14.1 kHz. We also observed courtship, where females produce in response to male courtship short clicks associated with wing flipping. This species specific calling and courtship song patterns are compared with songs of other cicadas of the C. montana complex.
Keywords: bioakustika; entomologija; favna; škržati